1970
DOI: 10.5424/sjar/201008s2-1347
|View full text |Cite
|
Sign up to set email alerts
|

Regulated deficit irrigation effects on yield, fruit quality and vegetative growth of ‘Navelina’ citrus trees

Abstract: An experiment on regulated deficit irrigation (RDI) was performed during two growing seasons (2007 and 2008) in a drip-irrigated orchard of Navelina/Cleopatra in Senyera (Valencia, Spain). Two RDI treatments, where water application was reduced to 40% and 60% of the «irrigation dose» (ID), were carried out during the initial fruit enlargement phase (Stage II, 17 th July to 2 nd September). The rest of the year they were irrigated at 110% ID. These treatments were compared with a control, where irrigation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
1
7
0
3
Order By: Relevance
“…The relationship found between the photochemical reflectance indices and fruit quality in September can be explained by the fact that this period is not only the time of the most severe water stress levels, but also is a critical time in terms of the physiological stage of fruit growth in citrus. Previous experiments on 'Clementina de Nules' and 'Navelina' citrus trees (Gasque et al, 2010;Castel, 1999, 2000) have shown that the effects of RDI treatments depend on the phenological period in which the water restriction is applied. During period II, summer (initial fruit enlargement), the application of RDI did not affect yield or fruit quality, whereas during period III (end of summer-autumn) it resulted in a decrease in yield, fruit size and fruit quality parameters due to a slower growth rate in the final stages of crop development.…”
Section: Remote Sensing Of Water Stress and Fruit Quality Using Primentioning
confidence: 98%
“…The relationship found between the photochemical reflectance indices and fruit quality in September can be explained by the fact that this period is not only the time of the most severe water stress levels, but also is a critical time in terms of the physiological stage of fruit growth in citrus. Previous experiments on 'Clementina de Nules' and 'Navelina' citrus trees (Gasque et al, 2010;Castel, 1999, 2000) have shown that the effects of RDI treatments depend on the phenological period in which the water restriction is applied. During period II, summer (initial fruit enlargement), the application of RDI did not affect yield or fruit quality, whereas during period III (end of summer-autumn) it resulted in a decrease in yield, fruit size and fruit quality parameters due to a slower growth rate in the final stages of crop development.…”
Section: Remote Sensing Of Water Stress and Fruit Quality Using Primentioning
confidence: 98%
“…In contrast, in Ribera Alta, groundwater and/or well water is pumped to irrigate the fields. The practice of deficit irrigation (Gasque et al, 2010;Ruiz Sanchez et al, 2010) is being promoted as a good water conservation practice. The last potential under-utilized water supply is recycling treated wastewater at least for irrigation purposes (Alcon et al, 2010).…”
Section: Water Supplymentioning
confidence: 99%
“…This can be deduced from the value of the corresponding coefficient in regression tree and from the fact that 76% of orchards in this group are irrigated. On the other hand, L1 and L2 orchards (< 25%) indicated that this practice is necessary and improves yield, according to Agustí (2000Agustí ( , 2003, González-Altozano & Castel (2003), García Petello & Castel (2004), and Gasque et al (2010).…”
Section: Lemonmentioning
confidence: 99%
“…When lower values or dry seasons occur, complementary irrigation is needed (Agustí, 2000(Agustí, , 2003. Irrigation absence mainly affects the fruit size, although the effect of this absence also depends on the phenological state (González-Altozano & Castel, 2003;García Petello & Castel, 2004;Gasque et al, 2010).…”
Section: Introductionmentioning
confidence: 99%